THE ANALYSIS OF MULTICHANNEL SYSTEMS WITH REFUSAL IN CHANNELS OF POWER SUPPLY OF THE AIRFIELD LIGHT-SIGNAL COMPLEX - Новачук, Л. В. (Science-based technologies, 2012)
Тhe analysis of basic defects of the modern systems of power supply of light signaling complex of aerodrome with the use of autonomous diesel-generators are conducted. Тhe analysis of multi-channel systems with rejections in the channels of electric power are conducted.